Template‐Assisted Epitaxial Growth of Ordered SnO2 Nanorods Arrays with Different Hollow Structures for High‐Performance Sodium Storage - Zhang, Xinyu; Kang, Qiaoling; Su, Mengfei; Song, Chuang; Gao, Feng; Lu, Qingyi (Small (Weinheim an der Bergstrasse, Germany), 2024)
Anode materials for sodium ion batteries (SIBs) are confronted with severe volume expansion and poor electrical conductivity. Construction of assembled structures featuring hollow interior and carbon material modification is considered as an efficient strategy to address the issues. Herein, a novel template‐assisted epitaxial growth method, ingeniously exploiting lattice matching nature, is developed to fabricate hollow ordered architectures assembled by SnO2 nanorods. SnO2 nanorods growing along [100] direction can achieve lattice‐matched epitaxial growth on (110) plane of α‐Fe2O3. Driven by the lattice matching, different α‐Fe2O3 templates possessing different crystal plane orientations enable distinct assembly modes of SnO2, and four kinds of hollow ordered SnO2@C nanorods arrays (HONAs) with different morphologies including disc, hexahedron, dodecahedron and tetrakaidecahedron (denoted as Di‐, He‐, Do‐, and Te‐SnO2@C) are achieved. Benefiting from the synergy of hollow structure, carbon coating and ordered assembly structure, good structural integrity and stability and enhanced electrical conductivity are realized, resulting in impressive sodium storage performances when utilized as SIB anodes. Specifically, Te‐SnO2@C HONAs exhibit excellent rate capability (385.6 mAh·g−1 at 2.0 A·g−1) and remarkable cycling stability (355.4 mAh·g−1 after 2000 cycles at 1.0 A·g−1). This work provides a promising route for constructing advanced SIB anode materials through epitaxial growth for rational structural design. An innovative template‐assisted epitaxial growth strategy is developed to fabricate different hollow ordered SnO2@C nanorods arrays (HONAs). When applied in sodium‐ion batteries, the optimal anode material presents a high reversible capacity of 613.4 mAh·g−1 after 100 cycles at 0.2 A·g−1, along with excellent rate capability and remarkable cycling stability (355.4 mAh·g−1 over 2000 cycles at 1.0 A·g−1).